HUBUNGAN MOTIVASI BELAJAR SISWA DENGAN HASIL BELAJAR DALAM PEMBELAJARAN PKn DI SEKOLAH DASAR - Fadhilah, Naylatul; Alwi, Elma; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research aim to see correlation student’s motivation in learning and learning outcomes in PKn at the fifth grade of Primary School in Cluster II Kecamatan Baso Kabupaten Agam. The type of this research is correlation research. The sample of this research is 98 students at the fifth grade of Primary School in Cluster II Kecamatan Baso Kabupaten Agam. The result of this research shows that there is a correlation between students motivation in learning and learning outcomes in PKn at the fifth grade of Primary School in Cluster II Kecamatan Baso Kabupaten Agam. It is proved by the value  rhitung = 0,785 > rtabel = 0,1986 and significant value 0,000 < 0,005, which means Ha is accepted. So, there is a significant correlation between students motivation in learning with learning outcomes in PKn at the fifth grade of Primary School in Cluster  II Kecamatan Baso Kabupaten Agam”.Keywords: students motivation in learning, learning outcomes